META-NARRATIVE OF SANSKRIT IN INDIAN ENGLISH WRITINGS - Dr. Shreeja Tripathi Sharma (International Journal of Innovations in Engineering Research and Technology, 2024)
Sanskrit has been the primary language and the receptacle of sublime expressions in early India. The language became an object of engagement for Indologists and Orientalists who began a series of translations of Sanskrit works in English and initiated an association that subsequently culminated in form of Indian English Writings. The gradual absorption of English in Indian culture became partly accountable for rendering original works of Sanskrit inaccessible due to incomprehensibility as well as distortions in translations and cultural misrepresentations. Yet, it was also the chief reason why crucial works of the Sanskrit tradition survived. It is in this context that this research paper analyses Sanskrit as an enduring source of influence in the genesis of the canonical tradition of Indian Writings in English.